Challenges, benefits, and ethical concerns of technology integration in teaching and learning: Perspectives from private and international school teachers - Govindarajoo, Mallika Vasugi V.; Nair, Subadrah Madhawa; You, Tan Jun; Ping, Cha Shi; Min, Chan Jia; Wee, Kelvin Wee Kai; Ying, Hwong Chee (Edelweiss Applied Science and Technology, 2025)
The integration of technology in education has transformed teaching and learning by enhancing engagement, accessibility, and efficiency. However, despite its benefits, challenges such as technological barriers, digital inequality, insufficient teacher training, and ethical concerns continue to hinder effective adoption. This qualitative study explores the benefits, challenges, and ethical considerations of technology integration in private and international schools in Johor Bahru. Using a qualitative approach, semi-structured interviews were conducted with ten teachers to gain in-depth insights into their experiences with technology in the classroom. Findings reveal that teachers perceive technology as a valuable tool for improving teaching efficiency, student engagement, and administrative management. However, limited infrastructure, work-life balance concerns, and lack of information and communication technology (ICT) training remain significant barriers. Ethical concerns such as privacy risks, unequal access, plagiarism, and online misconduct further complicate technology adoption. The study underscores the need for enhanced teacher training, institutional support, and clear policies to address these challenges. Recommendations include improving technical infrastructure, implementing ethical guidelines, balancing digital and traditional teaching methods, and ensuring better work-life balance for educators.